WRITINGS ABOUT THE SKY FOR MEN AT THE SEA - CONSIDERATIONS AND STUDIES ABOUT ASTROLOGY AND ASTRONOMY OF THE XV AND XVI CENTURIES - Gomes de Almeida, Simone Ferreira [UNESP] (Univ Estadual Paulista Julio Mesquita Filho, Fac Ciencias Humanas & Sociais, 2018)
The writing of the history of astronomy was conducted by a few key points: the relation of this knowledge to voyages of expansion and improvement of nautical, the differentiation of astrology and the questioning of the place of science and superstition for the study of the sky, as well as the construction of structures of this knowledge by the writings that unfolded the subject. All these topics were developed to a greater or lesser extent in the historiographical studies of the past decades about the science of the sky. Thus, this text deals with the astronomy of the fifteenth and sixteenth centuries as an object of historiographical studies that privileged certain aspects of this lore, often converging with the refusal - which was already explicit in the writings of the fourteenth century - of what came to be affirmed in the future as something totally unrelated to astronomy - astrology.
Keywords: Astronomy; Astrology; History of Science; Iberian Peninsula